Studies on gas sensing performance of pure and modified barium strontium titanate thick film resistors - Jain, G. H.; Patil, L. A.; Patil, P. P.; Mulik, Uttam P.; Patil, K. R. (Bulletin of Materials Science, 2007)
Barium strontium titanate ((Ba0.87Sr0.13)TiO3-BST) ceramic powder was prepared by mechanochemical process. The thick films of different thicknesses of BST were prepared by screen-printing technique and gas-sensing performance of these films was tested for various gases. The films showed highest response and selectivity to ammonia gas. The effect of film thickness on gas response was also studied. As prepared BST thick films were surface modified by dipping them into an aqueous solution of titanium chloride (TiCl3) for different intervals of time. Surface modification shifted response to H2S gas suppressing the responses to ammonia and other gases. The surface modification, using dipping process, altered the adsorbate-adsorbent interactions, which gave the unusual sensitivity and selectivity effect. Sensitivity, selectivity, thermal stability, response and recovery time of the sensor were measured and presented.
Keywords: (Ba0.87Sr0.13)TiO3 thick films; ammonia gas sensor; II2S gas sensor; selectivity; sensitivity

Sono-chemical synthesis of ZnO nano-particles and their application in hydrogen sulphide gas sensing - Khanna, P. K.; Kate, Kunal; Dhanabalan, K.; Banerjee, Shaibal; Reji, Nedunnkandathil; Shinde, S. D.; Jain, G. H. (Journal of Nanoscience and Nanotechnology, 2012)
Herein we describe synthesis of ZnO nanoparticles by using alkaline solution of ZnX2 (X = NO3, Cl) under ultrasound energy of 20 KHz. The reaction can be completed in about 1-2 hours. As prepared powders were analyzed by XRD measurement to find that the product is hexagonal phase pure ZnO. UV-Visible measurement of aq. solution showed absorption band at similar to 365 nm and photoluminescence (PL) indicated multiple bands in visible region due to deep traps owing to high temperature sintering. The hydrophilicity can be imparted by use of a suitable polyelectrolyte. Freshly prepared samples showed good dispersion in aqueous and alcoholic medium. The thick films derived from the ZnO nano-particles showed excellent sensing for hydrogen sulphide gas.
Keywords: Gas-Sensing; Sono-Chemical; synthesis; ZnO Nano-Particles